2003
DOI: 10.1161/01.cir.0000093279.36628.12
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulants (Thrombin Inhibitors) and Aspirin Synergize With P2Y 12 Receptor Antagonism in Thrombosis

Abstract: Background-This study was designed to determine whether (1) P2Y 12 antagonism synergizes with other antithrombotics and (2) anticoagulants (thrombin inhibitors) affect the antithrombotic activity elicited by P2Y 12 antagonism. Methods and Results-Thrombosis was achieved by perfusion of human and murine blood through type III collagencoated capillaries at arterial shear rate. CT50547, a direct-acting P2Y 12 antagonist, inhibited thrombosis in PPACK-but not heparin-anticoagulated human blood. In contrast, CT5054… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…However, when more than one of these targets was inhibited, pronounced antithrombotic activity was observed. In another experiment, when human blood was anticoagulated with an FXa inhibitor and perfused through a chamber in the real-time assay, we observed that P2Y 12 antagonism with clopidogrel did not affect the for 4 min and quantified as described [23]. mice demonstrate a cyclic thrombotic process in vivo, but only a qualitative difference (i.e.…”
Section: Platelet Monitoringmentioning
confidence: 79%
See 2 more Smart Citations
“…However, when more than one of these targets was inhibited, pronounced antithrombotic activity was observed. In another experiment, when human blood was anticoagulated with an FXa inhibitor and perfused through a chamber in the real-time assay, we observed that P2Y 12 antagonism with clopidogrel did not affect the for 4 min and quantified as described [23]. mice demonstrate a cyclic thrombotic process in vivo, but only a qualitative difference (i.e.…”
Section: Platelet Monitoringmentioning
confidence: 79%
“…A potent synergism between clopidogrel and anticoagulants [using either a direct thrombin inhibitor (Bivalirudin), a FXa inhibitor or a synthetic LMW heparin] has also been observed ( Fig. 2) [23,24]. While these results may have a simple explanation, resulting from the inhibition of fibrin formation by the anticoagulant, where fibrin contributes to thrombus stability under arterial shear rate [25], the emerging data indicate that the anti-thrombotic synergisms may originate from the complementation of the signaling pathways in platelets.…”
Section: Combination Antithrombotic Therapymentioning
confidence: 90%
See 1 more Smart Citation
“…We examined the role of MRP-14 in platelet thrombus formation under physiologic arterial shear conditions using a highly automated dynamic flow system (20,21). Thrombus formation was achieved by perfusion of anticoagulated blood labeled with rhodamine 6G through collagen-coated rectangular capillaries at an arterial shear rate of 625 s -1 .…”
Section: Deficiency Of Mrp-14 Attenuates Platelet Thrombus Formation mentioning
confidence: 99%
“…) was achieved and recorded as described previously with minor modifications (André et al, 2003b). Platelets were labeled in situ using rhodamine 6G (0.2 mg/ml) administered through the tail vein 10 min before visualization of the arteries.…”
mentioning
confidence: 99%